1987
DOI: 10.1139/f87-318
|View full text |Cite
|
Sign up to set email alerts
|

Production and Biomass Size Spectra in the Bay of Quinte, A Eutrophic Ecosystem

Abstract: From the 1940s on, the Bay of Quinte was subjected to increased point-source phosphorus loading. This and other stresses (exploitation, fish species invasion, and perhaps climate fluctuation) altered the productivity of the ecosystem and community structure. In the late 1970s, point-source loading was greatly reduced. At the same time, walleye (Stizostedion vitreum vitreurn) produced the largest year class ever recorded and surged to abundance greater than those seen in the 1950s before its collapse. Also, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…e. particle-sizeconversion efficiency, E, and the relationship between turnover rate and body size). Models sf this type can provide estimates of potential production for the entire community over various size classes and have been so applied to Lake Ontario (Borgmann 1982(Borgmann , 1985Minns et al 1987),…”
Section: Comprehensive Methodsmentioning
confidence: 99%
“…e. particle-sizeconversion efficiency, E, and the relationship between turnover rate and body size). Models sf this type can provide estimates of potential production for the entire community over various size classes and have been so applied to Lake Ontario (Borgmann 1982(Borgmann , 1985Minns et al 1987),…”
Section: Comprehensive Methodsmentioning
confidence: 99%
“…This is an illustration of the point made by Patten and Odum (1981) that organisms occupying positions near the apex of the Eltonian Pyramid of numbers can influence community structure and function to a degree disproportionate with their relative biomass, or contribution to community metabolism. This accounts in part for the attraction of contemporary workers to particle size theory (Spmles and Munawar 1986;Borgmann 1987;Minns et al 1987). A related approach was suggested by Patten (1985) who noted that living organisms store energy in direct proportion to their own biomasses and Margalef (1985) who noted that this storage (information content) relates inversely to turnover, i.e.…”
Section: Some Succession Theorymentioning
confidence: 97%
“…Resented tentatively at the SCOL symposium nearly two decades ago in connection with the "oligotrophicatisn7' process, this understanding has clearly been extended to nearshore regions within the Great Lakes basin, e. g . Bay of Quinte (Minns et al 1987), Long Point , and Green Bay ( H h s et al 1982). We believe that the ASPY case histories provide further documentation of broad ecosystemic responses to fishery exploitation, environmental changes, and species interactions.…”
mentioning
confidence: 99%
“…Leach et al (1987) estimated that potential or maximum sustained fish yield as a percentage of production averaged 21% (range 7-47%) in the Great Lakes. Minns et al (1987) reported a range of 11-45% for the Bay of Quinte, Lake Ontario. So assuming yield is 20% of production, total potential yield in Ontario was 42,900 tons, and anglers removed 54.5%.…”
Section: Production/biomass/yieldmentioning
confidence: 99%